Pengaruh Kualitas Pelayanan dan Kompetensi Karyawan Terhadap Kepuasan Nasabah Bank BJB Telagasari (Studi Kasus Nasabah BJB Telagasari) - Latif, Muhamad Septiaraya; Tuhagana, Aji; Apriani, Zenita (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Customer satisfaction is greatly influenced by several factors, namely service quality and employee competence, if the quality of service and employee competence work very well then customer satisfaction will be very good and vice versa. This study aims to analyze the effect of service quality and employee competence on customer satisfaction in the banking sector. The research method used is a descriptive and verification approach with a survey technique through a questionnaire distributed to 75 bank customers, the analysis uses multiple linear regression with the help of SPSS version 21. Based on the results of the study, it can be concluded that service quality (X1) is categorized as good, employee competence (X2) is categorized as good, customer satisfaction (Y) is categorized as good, service quality (X1) on customer satisfaction (Y) partially has a positive effect, employee competence (X2) on customer satisfaction (Y) partially has a positive effect, service quality (X1) and employee competence (X2) on customer satisfaction (Y) simultaneously have a positive effect, while the determination value is 0.545 or 54.5% and other values 0.455 or 45.5% are other variables outside the study.